PERBEDAAN HASIL BELAJAR SISWA YANG DIAJARKAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING DAN MODEL PEMBELAJARAN PROBLEM SOLVING PADA MATERI STATISTIKA UNTUK SISWA KELAS VIII SMP NEGERI 20 AMBON - Tronanawowoy, Dina Inggrid; Palinussa, Anderson Leonardo; Silitonga, R H Yanti (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
This study aims to find out: (1) the learning outcomes of students taught using the discovery learning model on statistical material for grade VIII students of SMP Negeri 20 Ambon; (2) student learning outcomes taught using problem solving learning models on statistical material for grade VIII students of SMP Negeri 20 Ambon; (3) differences in student learning outcomes taught using the discovery learning model and the problem solving learning model in statistical material for grade VIII students of SMP Negeri 20 Ambon. The type of research used is Quasi Experimental with a Nonequivalent Control Group design. The population in this study was all grade VIII students of SMP Negeri 20 Ambon, totaling 44 students using saturated sampling techniques, 22 students from class VIII-1 and 22 students from class VIII-2 were taken to be sampled. The instrument used in this study is a test question. The results showed that there were differences in the learning outcomes of grade VIII students of SMP Negeri 20 Ambon who were taught using the discovery learning learning model and the problem solving learning model on statistical material. This can be seen from the results of the t-test, namely the sig of value. (2-tailed) = 0.013 < α= 0.05 so that accepted and rejected.